Purchase and Redemption Decisions of Mutual Fund Investors of Variable Life Insurance-Using Quantile Regression - Wang, Nan Yu; Chen, Sen Sung; Huang, Chih Jen; Yen, Cheng Hsin (International Journal of Economics and Financial Issues, 2014)
We identified the relationship between purchase and redemption behavior of flow-return and flow-fund characteristics within different group investors by using Quantile regression, we found that insured investors have reflect better performance than non-insured investor in our study. However, there is no significant difference between non-insured investor’ purchase behavior and performance. In addition, regarding fund characteristics, the relationship between insured investors and fund expense ratios was stronger than it was among the noninsured investors. Low expense ratios attract new investors because of improvements in performance, which indirectly enhances the sensitivity of the relationship between fund flows and performance when performance is strong. Keywords: Variable Policies; Mutual Funds; Fund Performance; Investment Behavior; Quantile Regression JEL Classifications: C1; G2; M1